Navigating the digital dilemma: the impact of Internet addiction on social interaction among nursing students - Mudita R. Sharma; Manisha Gupta; Dolly John Shiju; Shatrughan Pareek (MGM Journal of Medical Sciences)
Background: With 4.57 billion people actively using the Internet worldwide, concerns about Internet addiction disorder (IAD) and its effects on daily life have become increasingly significant. This study investigates the intricate relationship between Internet addiction and face-to-face communication, focusing on how excessive online engagement influences traditional social interactions. It examines the association between Internet addiction and social interaction among nursing students in today’s digitally driven world. Materials and Methods: A quantitative research design was adopted, and data were collected from 128 nursing students using convenience sampling. The Internet Addiction Test (IAT) was employed to assess the severity of Internet addiction, whereas face-to-face social interactions were evaluated using a customized questionnaire. Results: The findings revealed a moderate level of Internet addiction among participants, with a mean IAT score of 45.7. A negative correlation (−0.32) was identified between IAT scores and the quality of face-to-face interactions, indicating that higher Internet addiction levels are associated with reduced interaction quality. Regression analysis further confirmed a significant negative correlation (−0.23) between IAT scores and the quality of social interactions. Although daily hours spent online demonstrated a positive but nonsignificant relationship (0.11) with interaction quality, a negative correlation (−0.17) was observed between the frequency of social media use and the quality of face-to-face interactions. Conclusion: This study underscores the significant impact of Internet addiction on face-to-face social interactions among nursing students. It emphasizes the need for targeted strategies to balance the benefits of digital connectivity with the preservation of meaningful interpersonal communication, providing valuable insights for future research and intervention.